Home advantage in football after moving to a new stadium: evidence from European professional teams - Leite, W.; Giardina, M.; Almeida, C. H.; Pollard, R. (International Journal of Sport and Exercise Psychology, 2023)
Familiarity with local conditions is considered one of the main causes of home advantage (HA) in sport, yet it has received little attention from the sports science community. This study aimed to establish whether moving to play in newly built stadiums influences the HA of European professional football teams. The sample comprised 98 teams from 25 different leagues affiliated with the Union of European Football Associations (UEFA). For each team, the analysis was done with six full seasons, three before and after the stadium relocation. A general linear model was fitted to the data including team ability as a covariate to calculate the HA. Tukey`s pairwise comparisons revealed that the adjusted HA did not differ between any pairs of seasons, demonstrating that moving to a new stadium did not change the HA. A complementary repeated-measure analysis was conducted to examine the relationship between HA and stadium attendance over the six seasons. Although there was a large-sized and significant increase in attendance after relocation (51.6%), a negligible correlation (rs = -0.02, p = 0.85) between the size of the increase and the change in HA was found. It was concluded that there is no consistent evidence that a change of stadium significantly affects the HA of professional football teams; nevertheless, there is likely to be a positive impact on revenue because of increased crowd support and interest from the local community. Building a new and modern stadium is a positive strategy that can be adopted by football clubs without the expectation of change in HA.